The ER-Localized Protein DFCP1 Modulates ER-Lipid Droplet Contact Formation - Li, Dongfang; Zhao, Yan G.; Li, Di; Zhao, Hongyu; Huang, Jie; Miao, Guangyan; Feng, Du; Liu, Pingsheng; Li, Dong; Zhang, Hong (Cell reports (Cambridge), 2019)
Very little is known about the spatiotemporal generation of lipid droplets (LDs) from the endoplasmic reticulum (ER) and the factors that mediate ER-LD contacts for LD growth. Using super-resolution grazing incidence structured illumination microscopy (GI-SIM) live-cell imaging, we reveal that upon LD induction, the ER-localized protein DFCP1 redistributes to nascent puncta on the ER, whose formation depends on triglyceride synthesis. These structures move along the ER and fuse to form expanding LDs. Fusion and expansion of DFCP1-labeled nascent structures is controlled by BSCL2. BSCL2 depletion causes accumulation of nascent DFCP1 structures. DFCP1 overexpression increases LD size and enhances ER-LD contacts, while DFCP1 knockdown has the opposite effect. DFCP1 acts as a Rab18 effector for LD localization and interacts with the Rab18-ZW10 complex to mediate ER-LD contact formation. Our study reveals that fusion of DFCP1-labeled nascent structures contributes to initial LD growth and that the DFCP1-Rab18 complex is involved in tethering the ER-LD contact for LD expansion. [Display omitted] •The ER protein DFCP1 redistributes from the ER to LDs upon induction of LD formation•Fusion of DFCP1-labeled nascent structures contributes to initial LD growth•BSCL2 regulates the dynamics and maturation of DFCP1-labeled structures•DFCP1 interacts with the Rab18-ZW10 complex to mediate ER-LD contact formation Li et al. used super-resolution GI-SIM imaging to reveal that during LD biogenesis, the ER-localized protein DFCP1 redistributes to nascent LD structures, which further fuse to form expanding LDs. DFCP1 acts as a Rab18 effector for LD localization and interacts with the Rab18-ZW10 complex to mediate ER-LD contact formation.